2022
DOI: 10.1038/s41598-022-08822-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ternary copper antimony sulfide via solventless thermolysis or aerosol assisted chemical vapour deposition using metal dithiocarbamates

Abstract: Copper antimony sulfide (Cu-Sb-S) has recently been proposed as an attractive alternative photovoltaic material due to the earth-abundant and non-toxic nature of the elements, high absorption coefficients and band gaps commensurate with efficient harvesting of solar photonic flux across multiple phases of Cu-Sb-S. These materials are therefore highly desirable and sustainable and scalable deposition techniques to produce them are of interest. In this paper, we demonstrate two facile, low-temperature and inexpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 69 publications
(77 reference statements)
0
31
0
Order By: Relevance
“…Lewis's research group has extensively explored the versatility of metal xanthates and thiocarbamates for the phase-pure preparation of various exotic multinary metal sulfides. [14][15][16][17] Similarly, Revaprasadu et al have also investigated the suitability of xanthates and thiocarbamates for the preparation of several important nanosized metal sulfides. [18][19][20] However, a thorough literature study has revealed that xanthates have not been explored for the preparation of technologically important Cu 2 GeS 3 nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…Lewis's research group has extensively explored the versatility of metal xanthates and thiocarbamates for the phase-pure preparation of various exotic multinary metal sulfides. [14][15][16][17] Similarly, Revaprasadu et al have also investigated the suitability of xanthates and thiocarbamates for the preparation of several important nanosized metal sulfides. [18][19][20] However, a thorough literature study has revealed that xanthates have not been explored for the preparation of technologically important Cu 2 GeS 3 nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note here that there are several reports in the literature, wherein despite the mismatch between the calculated and observed weight loss in TG, the complex serves as an efficient precursor for the synthesis of nanostructures by either solventless or solvent mediated routes. 26,32,36,44…”
Section: Thermal Studiesmentioning
confidence: 99%
“…31 Alternatively, reports suggest that high-purity Cu 12 Sb 4 S 13 (tetrahedrite) can easily be produced using a molecular precursor route. 15,32,33 and studied its photo-induced charge transfer characteristics. 10 In another experiment, diethylcarbamates of copper and antimony were successfully used for the solvothermal preparation of high-purity Cu 12 Sb 4 S 13 with multiply-voided morphology.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations